A new model for refrigerant boiling inside Brazed Plate Heat Exchangers (BPHEs). (December 2015) - Longo, Giovanni A.; Mancin, Simone; Righetti, Giulia; Zilio, Claudio
Highlights: This paper presents a new model for refrigerant boiling inside BPHE. The new model includes specific equations for nucleate and convective boiling. The model can be extended also to boiling with outlet vapour super-heating. The model reproduces experimental data with a MAPE around 20%. Abstract: This paper presents a new model for refrigerant boiling inside Brazed Plate Heat Exchangers (BPHEs) based on a set of 251 experimental data previously obtained by the authors which includes data points relative to HFC refrigerants (HFC236a, HFC134a, HFC410A), HC refrigerants (HC600a-Isobutane, HC290-Propane, HC1270-Propylene), and also a new low Global Warming Potential (GWP) HFO refrigerant (HFO1234yf). The new model includes specific equations for nucleate and convective boiling. The new model was compared against a set of 505 experimental data obtained by different laboratories, which includes HFC134a, HFC410A, HFC507A and HCFC22 data points with different plate geometries. The mean absolute percentage deviation between experimental and calculated data is around 20%.